The effect of rearing density on skeletal anomalies in zebrafish, Danio rerio (Hamilton, 1822) - Martini A; Boglione C; Huysseune A; Witten PE (country:PT, 2018)
Rearing density can affect the welfare of farmed fish. In aquaculture, inappropriate high stocking density alters the animals’ nutritional status, condition indexes, growth rate and blood composition and they are also correlated with skeletal malformations [1-3]. In zebrafish rearing density is reported to affect the male/female ratio [4], increase whole-body cortisol [5] and hierarchical dominance [6], but concerning the effect of rearing density on skeletal malformations literature is scarce. Ferreri [7] compared skeletal malformations in wild and reared zebrafish (0.2 ind/L), finding only slight differences between the two groups. This study examines skeletal malformations in zebrafish obtained from the same pool of breeders and reared at three different densities. Zebrafish (WT) were reared at 20 ind/L until 30 dpf. At 30 dpf, animals were transferred to a circulating-water system and reared until 90 dpf at three densities: high (HD=32 ind/L), medium (MD=8 ind/L) and low (LD=2 ind/L). Fish were fed twice per day ad libitum, with Artemia salina nauplii and with commercial food flakes (TetraMin®). Photoperiod and water temperature were 14L: 10D and 28°C, respectively. At the end of the experiment occurrence of skeletal malformations was evaluated based on single Alizarin red whole-mount staining for bone. Each fish was measured (standard length) and the occurrence of 113 types of possible malformations was registered. The HD group showed the highest malformative index (number of malformations per deformed fish), and the highest diversity in types of malformations. All specimens from each experimental group had at least one malformation. This conclusion holds even by excluding malformations of preural and ural vertebral bodies. These regions display a high degree of variability [7-8], and alterations may not be included in these malformations [7, 9]. The HD group had the highest numbers of malformations in the caudal region, similar to what is observed in farmed Atlantic salmon [10].